The gastro protective effects of Cibotium barometz hair on ethanol-induced gastric ulcer in Sprague-Dawley rats. Issue 1 (December 2016) - AL-Wajeeh, Nahla; Hajerezaie, Maryam; Noor, Suzita; Halabi, Mohammed; Al-Henhena, Nawal; Azizan, Ainnul; Kamran, Sareh; Hassandarvish, Pouya; Shwter, Abdrabuh; karimian, Hamed; Ali, Hapipah; Abdulla, Mahmood
Abstract Background Cibotium barometz is a medical herb used traditionally in the Malaysian peninsula for several ailments, including gastric ulcer. The aim of this study was assessment the anti-ulcer effects ofC. barometz hair on ethanol-induced stomach hemorrhagic abrasions in animals. Seven groups of Sprague Dawley (SD) rats were administered 10% Tween 20 in the normal control and ulcer control groups, and omeprazole 20 mg/kg and 62.5, 125, 250, and 500 mg/kg ofC. barometz hair extract in the experimental groups. After 60 min, the normal control group of rats was orally administered 10% Tween 20, while absolute ethanol was orally administered to the groups of ulcer control, omeprazole and experimental groups. Stomachs of the rats were examined macroscopically and histologically. Homogenates of stomachs were used to evaluate endogenous antioxidant enzyme activities. Results Rats pre-fed with plant extract presented a significant decrease in the sore area, increased pH of gastric contents and preserved stomach wall mucus compared to the ulcer group. Histologically, rats pre-fed withC. barometz hair extract showed mild to moderate disruptions of the surface epithelium while animals pre-fed with absolute ethanol showed severe disruptions of the stomach epithelium with edema and leucocyte penetration of the submucosal layer. A Periodic acid Schiff (PAS) staining revealed that each rat pre-treated with the plant extract displayed an intense uptake of stomach epithelial glycoprotein magenta color compared to the ulcer control group. Immunohistochemical analysis revealed that rats pre-fed with the plant extract showed an up-regulation of the heat shock protein 70 (HSP70) and down-regulation of Bax proteins compared to ulcer control rats. Homogenates of the stomach tissue demonstrated significant increases in the endogenous antioxidant enzymatic activity and decreased lipid peroxidation (MDA) in rats pre-treated withC. barometz hair extract compared with the ulcer control rats. In acute toxicity, the liver and kidney revealed no hepatotoxic or nephrotoxic effects histologically. Conclusions The gastric cytoprotective action ofC. barometz hair extract might be attributed to antioxidants, an increase in gastric pH, stomach mucus preservation, increased endogenous antioxidant enzymes, decreased lipid peroxidation, up-regulation of HSP70 and down-regulation of Bax proteins.